PERANAN MODAL SOSIAL MELALUI PENGEMBANGAN KELEMBAGAAN DAN PEMBERDAYAAN RUMAH TANGGA MISKIN DI DAERAH PESISIR (Studi Kasus: Rumah Tangga Di Kecamatan Koto IV Tarusan Kabupaten Pesisir Selatan) - Neng Kamarni (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2012)
The purpose of research include studying the characteristics of social capital in the communities especially poor fishermen fishing in the coastal areas, Kabupaten Pesisir Selatan, studying characteristic of social networks and institutional owned by poor households, which is the primary vehicle for empowerment, and to analyze the contribution and role of social capital to welfare of fishermen households in Kecamatan Koto IV Tarusan Kabupaten Pesisir Selatan, and to formulate and create a model for institutional development for the empowerment of poor fishermen.The regression results obtained influence SC (social capital) on the level of social welfare is positive, the higher the social capital of the area, the higher the welfare seaboard district. Kec. Koto XI Tarusan. So also with the HC (human capital) suggests that increased education will improve the welfare of the community. Effect of land will provide opportunities to increase the welfare of society. Variable Z (number of household members) suggests that the increase in the number of family members will reduce the level of social welfare.